The Perception Of Physics Education Students Towards The Use Of Online Lecture Applications During Covid-19 Pandemic - Rahmati Rahmati; Elmi Mahzum; Abdul Halim (Asian Journal of Science Education, 2021)
This study aims to determine the perception of physics education students on the use of online lecture applications during the covid-19 pandemic. The approach used in this research is a quantitative approach with descriptive research type. The population in this study were all students majoring in Physics education at USK FKIP who were active in the Even Semester of the 2020/2021 Academic Year and the sample in this study was 80 students of physics education. The sampling technique used is simple random sampling technique. Data collection was carried out using a closed questionnaire based on google form. The data analysis technique used in this study was the Likert's summeted rating procedure. The results showed that physics education students gave positive perceptions regarding the use of online lecture applications during the covid-19 pandemic.